Using Digital Learning Media as Information Literacy to Improve Learning Activity - Elya Nusantari; Marini Susanti Hamidun; Lilan Dama; Dewi Wahyuni K. Baderan; Chairunnisah J. Lamangantjo; Nur’Ain Lahaya (Postgraduate, University of Mataram, 2023)
The purpose of this study is to describe the use of digital learning media as a source of information literacy and student activity. Research methods using mixed methods. Data collection using instruments in the form of questionnaires and observation sheets. The data analysis used was editing, tabulating, analyzing, concluding. The results of research for information literacy of students that the aspect that has the highest interval is found in the fourth aspect, namely the ability individually or in groups to use information effectively to achieve certain goals with a value of 3.74 while the lowest aspect with a value of 33.00 in the second aspect is the ability to access information that needed effectively. This is in line with Izzatinnida’s research (2019) that the use of internet media as a learning resource consists of browsing or searching to obtain significant additional material outside of textbook subject matter. Teachers and their students can access this information as a learning resource. In the learning activities of students for meetings I and II there was an increase in every aspect. These aspects include based on the introduction, student orientation to problems, organizing students to study, guiding investigations, developing and presenting work, analyzing and evaluating problem-solving processes it can be concluded that information literacy and learning activities can be put to good use during learning and increase learning activities in supporting information